Designing an EFL vocabulary app for autonomous lexical learning - Lehmkuhl, Paulina (Activation-innovation-inspiration in (glotto) didactics, 2022)
This paper identifies key features crucial for design and development of vocabulary learning apps for English as a foreign language. Theories and models from (psycho)linguistics and multimedia design come together to provide a comprehensive point of departure for designing mobile apps. Taking the newly developed coursebook-corresponding app LexiFun for secondary EFL learners as an example, this paper also shows how such theories and models can be implemented into designing a digital tool for autonomous lexical learning for young secondary school students in Germany.